The assistant referees` activity in refereeing elite football: Preoccupations when not judging offside - Boyer, S.; MacMahon, C.; Récopé, M.; Rix-Lièvre, G. (Psychology of Sport and Exercise, 2020)
Objective: The purpose of this research was to study the preoccupations assistant referees had to participate in decision making about duels during football games.